Influencing Factors and Attractiveness of Shopping Mall to Mall Behaviour of People in Jakarta - Sebastian, Ernest Hasiolan; Purwanegara, Mustika Sufiati (Journal of Business and Management, 2014)
Abstract-The aim of this research is to understand the important factors of people in Jakarta when they going to shopping malls and the attractiveness of shopping mall that influencing shopping behaviour of  people in Jakarta. Masive growing of shopping mall in Jakarta made Jakarta to be a city with the most malls in the World, and it make the traditional market reduced. Leisure and completeness of a  shopping mall influenced the  Attractiveness of shopping mall and can be seen with the number of visitors in malls. Many factors of shopping mall considered by customers for choosing their favourite mall. The of the location of the shopping mall, mall shopping behaviour and also factors that make a mall or shopping center becomes more attractive to costumers. Many pro and contra about the growing of shopping mall in Jakarta, eventhough government of Jakarta is planning to forbid the property company to build mall in Jakarta by their regulations. Keywords: Mall Shopping Behaviour, Mall Attractiveness, Government Regulation, Leisure and Completeness, Location, Pro and Contra of Shopping Mall.